Foundations of college chemistry - Morris Hein (Wadsworth, 1993)
The book emphasizes the connection between chemistry and the lives of the students. Each chapter opens with a color photo relating the chapter to daily life. Each chapter contains a special section titled "Chemistry in Action," which shows the impact of chemistry in a variety of chemical applications.These essays and photos cover such topics as superconductors, food additives, photogray sunglasses, scuba diving, and the restoration of the Statue of Liberty. Atoms, molecules, and reactions are all an integral part of the chemical nature and matter. The book continues to present new material at a level appropriate for the beginning student by accentuating nomenclature, composition of compounds, and reaction before moving into the details of atomic structure. The examples show how to incorporate fundamental mathematical skills, scientific notation, and significant figures by following the rules consistently. A list of "Concept in Review" given at the end of each chapter guides in determining the most important concepts in the chapter. A "Glossary-Index" is provided to help students locate key terms and find the definition in context. Answers to the mathematical problems are given in Appendix V. Review Exercises for each chapter have been compiled at the end of the book